The Effect of Cigarette Smoke Exposure in the Fetal Growth and Fetal Development of Mice (Mus musculus) - Endy Novryan Ridwan; Martono Tri Utomo; Harianto Notopuro (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2020)
Introduction: This research aims to investigate and observe the effect of cigarette smoke exposure in the fetal growth and fetal development of mice (Mus musculus).  Methods: This was an experiment with post-test only control group design. The sample of the research was 36 pregnant mice which were randomly divided into 2 groups: control group (K) pregnant mice which inhaled ambient air without cigarette smoke exposure, and treatment group (P) pregnant mice which were given cigarette smoke exposure for 14 days with 2 bars of cigarette each day.  Results: The results showed a significant difference in the fetal birth weight between the group exposed to cigarette smoke (p < 0.05) compared with the control group. Fetal defect and stillbirth were not found in this research. Conclusion: The exposure of cigarette smoke gave negative effects of fetal growth and development because of the free radicals generated.